Generation, transfer and utilization of information on natural rubber : A functional model - Thomas K K (Proceedings of the 15th Plantation Crops Symposium, PLACROSYM XV, 10-13 December 2002, Mysore .pp.738-751.)
The components and sub-systems of an ideal natural rubber (NR) information transfer system by which innovations covering all relevant aspects of NR production, processing and marketing reach the users expeditiously using all communication channels with adequate feedback are presented. A new scientific extension interaction linkage of agricultural service agencies and policy makers is observed among users. In the NR information system, four sub-systems of generation, documentation, extension and utilization are identified. International agencies like ANRPC, IRRDB, IRSG etc., Rubber Research Institutes like RRIM, RRISL, RRII, IRCA etc., Universities, public and private R&D institutions are among the NR information generation agencies. The generated bibliographically in the documentation sub-system. The extension sub-system ensures the constant information flow in a readily comprehensible form to the growers through general extension workers and to manufacturers through technology consultants with regular feedback to the generating sub-system. In the utilization sub-system, the end users accept and adopt the information and their experience becomes the feedback input to the generation sub-system.
Keywords: Natural rubber